2005
DOI: 10.1007/s11373-004-8183-7
|View full text |Cite
|
Sign up to set email alerts
|

T cell responses to allogeneic human mesenchymal stem cells: immunogenicity, tolerance, and suppression

Abstract: Human mesenchymal stem cells (MSCs) were evaluated for their ability to activate allogeneic T cells in cell mixing experiments. Phenotypic characterization of MSCs by flow cytometry showed expression of MHC Class I alloantigens, but minimal expression of Class II alloantigens and costimulatory molecules, including CD80 (B7-1), CD86 (B7-2), and CD40. T cells purified from peripheral blood mononuclear cells (PBMCs) did not proliferate to allogeneic MSCs. Lack of response was not due to a deficiency of costimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
398
1
17

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 544 publications
(442 citation statements)
references
References 31 publications
26
398
1
17
Order By: Relevance
“…Indeed, this discrepancy between in vitro and in vivo MSC suppression studies is reminiscent of the conundrum regarding the mechanisms of suppression of murine Tregs, which also display distinct behaviours in vitro and in vivo [23]. Our results also highlight important differences between mouse and human MSCs [24,25]. Glennie et al [25] reported that human MSC-mediated inhibition induces an unresponsive T cell profile that can be reverted by the addition of exogenous IL-2.…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, this discrepancy between in vitro and in vivo MSC suppression studies is reminiscent of the conundrum regarding the mechanisms of suppression of murine Tregs, which also display distinct behaviours in vitro and in vivo [23]. Our results also highlight important differences between mouse and human MSCs [24,25]. Glennie et al [25] reported that human MSC-mediated inhibition induces an unresponsive T cell profile that can be reverted by the addition of exogenous IL-2.…”
Section: Discussionmentioning
confidence: 63%
“…In vitro, both MSCs and NPCs are MHC-I low/medium and MHC-II negative (Klyushnenkova et al, 2005;Le Blanc et al, 2003;Pluchino et al, 2005Pluchino et al, , 2009a, but upregulation of MHC-I and -II expression is observed after long-term neurosphere expansion (Laguna Goya et al, 2011;Odeberg et al, 2005) or NPC exposure to proinflammatory cytokines such as interferon (IFN)-γ or tumor necrosis factor (TNF)-α (Johansson et al, 2008). Under basal growth conditions the co-stimulatory molecules CD80/ B7.1, CD86/B7.2 and CD40 are also absent in both MSCs and NPCs (Odeberg et al, 2005;Tse et al, 2003).…”
Section: In Vitro Stem Cell Immunogenicitymentioning
confidence: 99%
“…The MSC capacity of inducing proliferative responses by allogeneic PBMC represents a controversial issue [14,25,26,28]; notably, however, both human and murine MSC are generally considered to be poorly immunogenic cells. MSC can also produce a variety of growth factors, cytokines, chemokines and proteases that are likely to play a role either in their immunomodulatory or in their migratory function [29][30][31].…”
Section: Immunological Phenotype and Functions Of Mscmentioning
confidence: 99%